Potential Role of Probiotics for Sustainability in Rural India - Cencič , Avrelija; Langerholc, Tomaž; Roy, Kislay (Journal for Geography, 2010)
Probiotics (greek “for life”) have been recognized and explored for over a century. Metchnikoff’s pioneering work was converted into commercial reality in the 1950s, and since then many probiotics’ benefits have been described. Nowadays they have already found place as a food supplement and as a preventive or curative drug. The term probiotic describes a variety of microorganisms which can colonize the host and have health improving effects on it. Since it is a natural and comparably affordable product even for people with low incomes, it could be introduced into the diet of people living in the Indian rural areas. The biggest obstacles for this are education about their use and technology to prepare them in a convenient form for domestic use. Regular use could improve the quality of live and reduce the dependence on drugs and medical expenses.